Desain Katalog Online dalam Kepuasan Pemustaka di Perpustakaan Universitas Negeri Padang - Wiradani, Oksa; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this paper is to describe the design of an online catalog of the Library UNP: searching procedures, item information, colors and layout. Based on data analyzing, it can be concluded: (1) searching procedure in the design of an online catalog is still focused only on the search through the title alone and the lack of socialization of online catalog to the users, not on the details of the process of online books borrowing, and the lack of alternatives that leads title on the desired title, (2) the information in the online catalog is not yet clear and detailed, i. e. information such as the location where the books are stored, the classification of library materials have accurate information, and the lack of notification of the latest book in the library, (3) the use of color is less clear and make the users also less clear in getting information, and (4) layout on the composition of the title not neat in appearance yet. Keywords: online catalog; search procedure; item information; color; layout